Analysis of Efficiency and Reflexivity of Bank Syariah Indonesia With Islamic Values - Roikhan Mochamad Aziz; Jesyca Lulu Precilia Putri; Rahma Nurcahyani Safitri; Qonita Lutfiah; Mohammad Rafli Syahputra (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2023)
The purpose of this study is to measure the level of efficiency and reflexivity of Bank Syariah Indonesia (BSI) by using sharia values in the city of South Tangerang for the 2019-2021 period. This study used Data Envelopment Analysis (DEA) to measure the efficiency level of each BSI. The input variables in this study used deposits and assets. Meanwhile, the output variables in this study used financing and operating income. The results of this study show that the effectiveness of BSI is volatile. Bank Syariah Indonesia recorded an efficiency level of 60.8% in 2020-2021 and was also inefficient. This study also provides recommendations to overcome the inefficiency of Bank Syariah Indonesia. Sharia values and performance have differences for each Bank Syariah Indonesia